Skyscrapers, celadon, and kimchi a Korean notebook - Pantoja-Hidalgo, Cristina 1944- (Diliman, Quezon City University of the Philippines Press, 1993)
Author's account on her stay in Seoul, Korea from 1981-1984.
"Revised edition"--P. ix.
Keywords: Hidalgo, Cristina Pantoja -- Travel -- Korea (South); Korea (South) -- Description and travel